Time in Russian and Japanese Lingo-cultures - N. E. Gorelova (Vestnik MGIMO-Universiteta)
The article highlights the concept of "time" as the most important axiom which is a part of linguocultural worldview of different nations, that also allows us to consider this concept in terms of its cultural distinctive potential. In its turn, the definition of the limits and possibilities of matching cultures by comparing their lingvocultural axioms enables us to refine the boundaries of their communicative interactions, identifying areas of understanding /misunderstanding and the most constructive interaction /potentialproneness to conflict. Cultural differences in understanding the time could be considered in two main directions: first, each culture performs the calculation of time in its own way; secondly, the way to decompose the time, its "segmentation" also creates a significant originality of unique linguocultural pictures of the world. These features are interrelated and interdependent, therefore it is reasonable to combine them under the title "time attitude." It goes without saying that, the attitude towards time in each linguoculture formed for many centuries, being therefore historically conditioned. In this case, axiological aspect in the attitude towards time should be mentioned, which is also associated with the reflection in this concept of the socially- approved values of different levels (ethical, aesthetic, religious, etc.). Consequently, we are talking about a concentrated expression of the important world paradigms in the concept of “time", which are related to value-sense orientation and social psychology segments, that are projected on the individual consciousness in the process of enculturation. The specificity of the Japanese culture is usually described within the overall paradigm of the relations between East and West, considered as a synthetic and analytical way of perceiving the world. These relations - are relations between two independent, different systems of traditions, meanings and world-views. The question of their commensuration is one of the key questions for the theory and practice ofintercultural communication, considering the influence of cultural differences on the run of the communicative event, its "success" or "failure." "Time attitude" is the most important linguocultural "axiom", allowing not only to recognize the specificity of the world picture of Japanese culture representatives, but also to highlight the clear criteria for its possible comparison with the counter-agents of the communication, to describe the "intersection point" and "point of mutual exclusionemerging form comparison of Japanese and Russian linguocultures, their peculiar" time attitude."